ІНТЕГРАЛЬНІ МОДЕЛІ ОЦІНКИ ЙМОВІРНОСТІ БАНКРУТСТВА СТРАХОВИКА У СУЧАСНИХ УМОВАХ - Налукова, Наталія Ігорівна; Гузела, Михайло Петрович (Науковий журнал «Світ фінансів», 2018)
Налукова Н. І., Гузела М. П. Інтегральні моделі оцінки ймовірності банкрутства страховика у сучасних умовах. Аргументовано, що оцінка ймовірності банкрутства страхових компаній в сучасних умовах господарювання дає змогу визначити не лише реальний стан ведення бізнесу, а й виявити критичні моменти у діяльності страховиків. В основі проведеного аналізу схильності страхової компанії до банкрутства використано дискримінантні моделі ймовірності банкрутства, які застосовуються як звичайними підприємствами, так і страховиками. За основу однофакторного дискримінантного аналізу взято модель, котра дає змогу оцінити загальний стан страховика за окремими критеріями-показ-никами, без використання вагових коефіцієнтів та граничних значень. Здійснено огляд методик оцінки ймовірності банкрутства та їх порівняльну характеристику, визначено чинники проблем використання зарубіжних дискримінантних моделей в Україні. Налукова Н. И., Гузела М. П. Интегральные модели оценки вероятности банкротства страховщика в современных условиях. Аргументировано, что оценка вероятности банкротства страховых компаний в современных условиях позволит определить не только реальное состояние ведения бизнеса, но и выявить критические моменты в деятельности страховщиков. В основе проведенного анализа склонности страховой компании к банкротству использованы дискриминантные модели вероятности банкротства, применяемые как обычными предприятиями, так и страховщиками. В основе однофакторного дискриминантного анализа - модель, которая позволяет оценить общее состояние страховщика по отдельным критериям-показателям, без использования весовых коэффициентов и граничных значений. Осуществлен обзор методик оценки вероятности банкротства и их сравнительная характеристика, определены факторы проблем использования зарубежных дискриминантных моделей в Украине. Nalukova N., Huzela M. Integrated models for evaluating the probability of insurer bankruptcy in modern conditions.Introduction. Assessment of the probability of insurance companies insolvency in modem conditions will determine not only the real state of doing business, but also identify critical moments in the activities ofinsurers.Purpose. The purpose of the article is to assess the probability of bankruptcy of a functioning insurance company on the basis ofmodels used in world practice.Results. The authors argue that the assessment of the probability of insurance companies insolvency in modern economic conditions will determine not only the real state of doing business, but also identify critical moments in the activities ofinsurers. The basis of the analysis of the insurer's predisposition to bankruptcy is discriminant bankruptcy probability models used by both ordinary enterprises and insurers. Based on the one-factor discriminant analysis, a model is developed which enables us to assess the general state of the insurer according to individual criteria-indicators, without using weight of coefficients and values of indicators.. An overview of the methods forassessing the probability of bankruptcy and their comparative characteristics is reviewed, the factors of problems ofthe use offoreign discriminatorymodels in Ukraine are determined.Conclusion. A critical assessment ofthe prevailing in foreign practice and the theory methodological approaches to the analysis of the bankruptcy probability allows us to conclude that some models are contradictory because, with the simultaneous use of them, it is possible to obtain conclusions opposite to each otherregarding the bankruptcyprobabilityofa particularentity.Despite some disadvantages, these models have high probability of evaluation and are very effective in practice. Discriminant models can be used to confirm the results both separately and in aggregate, however, with a certain correction. The most significant relationship between models in dynamics, because one-time analysis may not give correct results. All models contain a set ofdiffer-entindicators thathave territorial specificity, and none ofthem can claim to be universal.